ARTIFICIAL INTELLIGENCE IN BIOMEDICAL NANOTECHNOLOGY: FROM DIAGNOSIS TO THERAPY OPTIMIZATION - Choi Seojin; Sabrina Doudou; Muntasir Muntasir (Journal of Biomedical and Techno Nanomaterials, 2026)
The integration of Artificial Intelligence (AI) with biomedical nanotechnology is revolutionizing medical diagnostics and therapy optimization. The combination of AI’s computational power with the unique properties of nanomaterials enables more accurate disease detection, personalized treatment plans, and optimized therapeutic outcomes. Traditional diagnostic techniques often suffer from limitations in sensitivity, specificity, and the ability to offer personalized treatments. Nanotechnology, particularly through the development of nanoparticle-based systems, offers significant improvements in targeting, drug delivery, and imaging. AI can further enhance these capabilities by enabling real-time data analysis, predictive modeling, and personalized medicine approaches. This research explores the applications of AI in biomedical nanotechnology, focusing on its role in diagnosis, therapy optimization, and the potential for improving patient outcomes. The study employs a comprehensive review of existing literature, case studies, and computational models to assess the impact of AI-driven nanotechnologies in clinical settings. The results highlight the promising outcomes in disease diagnosis, particularly in oncology, and the potential for AI to optimize therapeutic strategies by analyzing large-scale patient data. In conclusion, the integration of AI and biomedical nanotechnology offers substantial advancements in precision medicine, facilitating more accurate, efficient, and personalized healthcare solutions.